Diagnostic Accuracy of complete Blood Count versus Serum Ferritin in Diagnosis of iron deficiency Anemia in Pregnant Women - Rabia Wajid, Amna Ahsan, Saira Fayyaz, Nadia Sehar, Hina Masood, Rizwana Tariq, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of confirmation of iron deficiency anemia in pregnant female on serum Ferritin who are labeled to have iron deficiency anemia on CBC in third trimester. Study Design: Cross-sectional study Study duration: October 2021 to March 2022. Setting: Department of Obstetrics & Gynecology Lady Willingdon Hospital. Patients and Methods: A total of 200 patients who came to OPD were selected. Detailed history was obtained from patients and physical examination performed. CBC and serum ferritin was determined for every patient. All data was entered into the especially designed proforma. Results: Anemia was diagnosed in 74(37%) women. Highest frequency of anemia was seen in women in age group 20-30 years (33.78%), and in women with household income of Rs.15000/- to 50000/- per month. Mean hemoglobin of women was 11.41±1.05 gm. /dl. Mean MCV of women was 83.12±8.45 fl. Minimum and maximum MCV was 68 and 95 fl respectively. Mean serum ferritin level of women was 13.14±2.34 µ/l .Anemia was diagnosed in 75(37.50%) women as per complete blood count criteria. Anemia was diagnosed in 74(37%) women as per serum ferritin level criteria. Practical implication: This study will significantly contribute to the understanding and management of iron deficiency anemia in pregnant women, particularly during the third trimester. By confirming diagnoses through serum Ferritin tests in addition to complete blood count (CBC), the study can enhance the accuracy of diagnosis and treatment. Accurate detection of iron deficiency anemia will allow for more targeted and efficient treatment, thereby improving maternal and fetal health outcomes. Furthermore, this research could inform public health policies and intervention strategies aimed at preventing and managing iron deficiency anemia in pregnancy, ultimately improving the overall well-being of the community. Conclusion: Results of this study revealed that Serum ferritin level is a better diagnostic test for early detection of iron deficiency anemia in pregnant women. Keywords: Confirmation, Iron deficiency, Anemia, Pregnant, Serum Ferritin, Complete blood Count, Third trimester.